Methodology for assessing the GPS receiver performance of agricultural use under kinematic condition - Machado, Thiago M. [UNESP]; Molin, José P.; Povh, Fabrício P.; Salvi, José V. (FapUNIFESP (SciELO), 2010)
Activities that use Global Navigation Satellite System (GNSS) are countless and the most used one is the Global Positioning System (GPS) developed by the United States. In precision agriculture there are demands for static and cinematic positioning with distinct levels of accuracy for different applications; nevertheless cinematic performance data are not available as manufacturers of GPS receivers present only static performance information. For this reason it was developed an instrumented vehicle to test a methodology of performance evaluation of GPS receivers in kinematic conditions, which is representative to agricultural operations. A set of instrumentation was composed and used for collecting data under variable speed and rotation direction. Tests were conducted showing that the methodology allows to measure accuracy and precision, but improvements have to be implemented on the instrumentation equipment for long term tests.
Metodologia para avaliação do desempenho de receptor de gps de uso agrícola em condição cinemática
Keywords: GPS; Kinematic tests; Precision agriculture